PELAYANAN HEMODIALISIS YANG BAIK BERHUBUNGAN DENGAN TINGKAT KEPUASAN PASIEN - Maria Esti; Sri Arini; Masta Hutasoit (Universitas Jenderal Achmad Yani Yogyakarta, 2014)
Background: There has been an increased number of patients with Chronic Kidney Disease. These patients maintain their quality of lifes by undergoing hemodialysis. To achieve patients’ satisfaction, hemodialysis unit in Wates General Hospital is required to provide the best service quality. Objective: To investigate the correlation between hemodialysis service quality and the patients’ satisfaction level Method: This research was a non-experimental study with cross sectional approach. Study involved 25 patients, who were recruited through a total sampling. Data were collected using questionnaires. Result: Most of the patients (84%) perceived the service was satisfactory. In term of satisfaction level, 84% of the patients felt satisfaction with the hemodialysis service. Kendall’s tau test revealed that there was a strong correlation between hemodialysis service and patient’s satisfaction (p-value= 0.042) with coefficient correlation of 0.702. Conclusion: There was a significant correlation between hemodialysis service and the patients’ level of satisfaction. Nurses should maintain the service provided in accordance with the standart operating procedures. Key words: Hemodialysis service, level of satisfaction